Health Education for Preconception Women's Care Using Leaflet Media in Wedding Preparation - Dian Wahyu Rahmawati; Faizah Betty Rahayuningsih (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
Educating women on aspects like physical changes, reproductive health, nutrition, fitness, and other crucial elements pertinent to marriage preparation through health education can offer accurate and updated information. The objective was to understand how health education through leaflet media impacts the knowledge and attitudes of women preparing for marriage. The research method employed a quantitative approach with a pre-experimental design, specifically a one-group pretest posttest design. This research will take place in September 2023 and is located at the Plupuh I Sragen health center. The study involved 30 adolescents divided into two intervention groups: Pre Test and Post test, utilizing pamphlets as the educational medium. Data analysis utilizes independent sample T-tests . The analysis revealed significant results in both groups: the Pre Test group with a mean of 1.40 ± 0.498 and the Post test group with a Mean of 1.73 ± 0.450. The analysis exhibited a P-Value of 0.009 (< 0.05), indicating a noticeable influence of health education using leaflet media on the knowledge and attitudes of women in their childbearing years preparing for marriage. In conclusion, utilizing leaflets for education purposes can serve as an effective alternative strategy in providing comprehensive and impactful information during marriage preparation and researchers suggest combining leaflets with other educational media so that the process of providing education is more optimal Keyword: Health education, Leaflet, Marriage knowledge, Women of childbearing age